2009
DOI: 10.1111/igc.0b013e3181a12fb9
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features in Endometrial Carcinoma Associated With Lynch Syndrome in China

Abstract: Some clinicopathological features of Lynch syndrome-associated endometrial carcinoma, such as early onset and multiple primary carcinomas are similar in the Chinese and American/European populations. However, the Chinese population had a unique family cancer distribution that included lung and breast cancers. Well-differentiated grade and good prognosis imply better biobehavior of Lynch syndrome-associated endometrial carcinoma in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
4
22
1
Order By: Relevance
“…To our knowledge, there was only one report of an association of diabetes with HNPCC-associated cancer, which describes that the prevalence of diabetes was not different between those with HNPCC and those without HNPCC. 11 The result of our study is consistent with that in this previous study. 11 This finding should be confirmed in a larger population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, there was only one report of an association of diabetes with HNPCC-associated cancer, which describes that the prevalence of diabetes was not different between those with HNPCC and those without HNPCC. 11 The result of our study is consistent with that in this previous study. 11 This finding should be confirmed in a larger population.…”
Section: Discussionsupporting
confidence: 93%
“…11 The result of our study is consistent with that in this previous study. 11 This finding should be confirmed in a larger population.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently with previous studies (14,16), no differences in the prevalence of DM or other chronic illnesses between the study groups were identified in the current study. With regard to BMI and other co-morbidities, the similarities between LS and sporadic EC patient cohorts may imply that sporadic and hereditary EC patients share a common risk factor profile.…”
Section: Discussionsupporting
confidence: 93%
“…These studies have suggested that EC women with a family history of CRC or suspected LS appear to be obese less often compared with EC women with no CRC family history (14)(15)(16)(17)(18). However, Lynch mutation carriers with EC have also been reported to be more obese compared with women with sporadic EC (16), whereas others (13) have reported no significant difference in BMI between these two patient groups, which is in line with the results presented in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation